Aplikasi Pengisian Data Alumni Prodi Teknik Universitas Islam Lamongan Berbasis Android - Megawati Indriani; Miftahus Sholihin; Nurul Ftria ApriLliani (Joutica, 2017)
The rapid technological developments at this time had impact on all aspects of human life. The impact that is clearly visible is that the technology has made it easier to assist all human activities. There is no doubt that now all the things that used to be done manually has now been changed into automatically. The technology allows the users to search for information easily, one of information is about alumni profile data information. Alumni profile database filling application can be done easier for the alumni to access variety of information. As one of the developing universites, Lamongan Islamic University has many alumni therefore it is needed alumni profile database filling application to facilitate the alumni to gain the information. Inside alumni profile database there are “Forum” menu and also “Info Lowongan Kerja” menu that can make the alumni easier to find a job and keep in touch with other students. This alumni profile database filling application can only be used by the alumni from Study Program of Engineering by using NIM as a username and password. Alumni profile database filling application is created using Android system and MySQL database. The results of the test demonstrate that the application works well.